ANALISIS KTNERIA PEMASOK PADA PROYEK PEMBANGUNAN GEDUNG UNIVERSITAS PENDIDIKAN GANESHA DENGAN PENDEKATAN DATA ENVBLOPMENT ANALYilS (DEA) - , Fitriana, Dr. Kuncoro Hartowidodo, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Suppliers, as part of supply chain system, are expected to have a good performance in order to reach the mutual goal. As one of leading construction companies, PT Adhi Karya Construction Division IV has many raw material suppliers. It is needed to analyse the performance of suppliers as a tool for decision making. The objective of this research is to analyse the performance of concrete sand, bricks, and corals suppliers using data envelopment analysis (DEA) approach. DEA could analyse relative efficiency level of decision making units (DMUs). It is a quantitative, nonparametric and multifactorial method with many inputs and outputs so that it could analyse the performance for each supplier. The result shows that the most efficient suppliers are PT Ingtraco in supplying concrete sand, bricks, and corals, UD Merpati in supplying concrete sand and bricks, UD Buana Indah in supplying bricks and corals, and CV Sumber Jati in supplying corals. The efficiency improvement of inefficient suppliers can be obtained by increasing supply, improving delivery time, also by lowering the price of concrete sand, bricks, and corals supply.